Regional Variation in Patients and Outcomes in the Treatment of Preserved Cardiac Function Heart Failure With an Aldosterone Antagonist (TOPCAT) Trial. Issue 1 (6th January 2015) - Pfeffer, Marc A.; Claggett, Brian; Assmann, Susan F.; Boineau, Robin; Anand, Inder S.; Clausell, Nadine; Desai, Akshay S.; Diaz, Rafael; Fleg, Jerome L.; Gordeev, Ivan; Heitner, John F.; Lewis, Eldrin F.; et al.
Abstract : Background—: Treatment of Preserved Cardiac Function Heart Failure With an Aldosterone Antagonist (TOPCAT) patients with heart failure and preserved left ventricular ejection fraction assigned to spironolactone did not achieve a significant reduction in the primary composite outcome (time to cardiovascular death, aborted cardiac arrest, or hospitalization for management of heart failure) compared with patients receiving placebo. In a post hoc analysis, an ≈4-fold difference was identified in this composite event rate between the 1678 patients randomized from Russia and Georgia compared with the 1767 enrolled from the United States, Canada, Brazil, and Argentina (the Americas). Methods and Results—: To better understand this regional difference in clinical outcomes, demographic characteristics of these populations and their responses to spironolactone were explored. Patients from Russia/Georgia were younger, had less atrial fibrillation and diabetes mellitus, but were more likely to have had prior myocardial infarction or a hospitalization for heart failure. Russia/Georgia patients also had lower left ventricular ejection fraction and creatinine but higher diastolic blood pressure (all P <0.001). Hyperkalemia and doubling of creatinine were more likely and hypokalemia was less likely in patients receiving spironolactone in the Americas with no significant treatment effects in Russia/Georgia. All clinical event rates were markedly lower in Russia/Georgia, and there was no detectable impact of spironolactone on any outcomes. In contrast, in the Americas, the rates of the primary outcome, cardiovascular death, and hospitalization for heart failure were significantly reduced by spironolactone. Conclusions—: This post hoc analysis demonstrated greater potassium and creatinine changes and possible clinical benefits with spironolactone in patients with heart failure and preserved ejection fraction from the Americas. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00094302. Abstract : Supplemental Digital Content is available in the text.